Tinjauan Yuridis terhadap Penerapan Ganti Rugi Akibat Wanprestasi Debitur dalam Perjanjian Kredit - As-Sifa Pebrianti; Salwa Fauziyah Anwar; Ardhita Aulia Utari; Shabrina Najla Ingga Jayasti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
A credit agreement is a common legal instrument in banking and financing activities that regulates the rights and obligations of creditors and debtors. In practice, debtor default often occurs when payment obligations are not fulfilled, fulfilled late, or performed contrary to the agreed terms, causing losses to creditors. This study analyzes the application of compensation for debtor default in credit agreements based on Article 1243 of the Indonesian Civil Code and examines legal remedies available to creditors. This research uses a normative legal method with statutory and case approaches. Data were obtained through library research, including legislation, legal literature, scholarly journals, and relevant court decisions. The results show that compensation claims may be submitted when there is a valid agreement, a proven breach of contract, a formal notice of default, and losses that have a direct causal relationship with the debtor’s breach. Compensation may include costs, damages, and interest. Creditors may pursue settlement through litigation or non-litigation mechanisms, including credit restructuring. Therefore, compensation for breach of contract functions as legal protection for creditors, strengthens legal certainty, and maintains a balance of rights and obligations between parties in credit agreements in resolving credit disputes fairly, proportionally, and in accordance with law.